Cooling and heating season performance of an open counterflow heat-source tower heat pump system in high-humidity climates: An experimental and numerical study - Xinhao Liu; Peng Liu; Dinggao Xiao; Yuan Li; Shuangying Yang (PLoS ONE, 2026)
The cooling and heating season performance of an open counterflow heat-source tower heat pump (HTHP) system in high-humidity climates is investigated through an integrated experimental and numerical study, focusing on its year-round operation under typical conditions. The heat and mass transfer models for summer and winter were validated using measured data. Results show that increasing the inlet air temperature in summer enhances latent heat transfer by 25% but reduces sensible heat transfer by 31%. Raising the water temperature from 28.0 °C to 34.0 °C resulted in a 20.7% increase in latent heat transfer and a 16.7% decrease in sensible heat transfer, thereby increasing the latent heat ratio to 87.19%. In winter, increasing the inlet air temperature from −1.0 °C to 7.0 °C enhanced sensible but reduced latent heat transfer. Higher solution temperatures reduced total heat transfer, and the latent heat ratio dropped to 18.2%. The inlet air humidity ratio had a greater effect on sensible heat transfer in summer, and the opposite in winter. Increasing the inlet solution mass flow rate enhanced the total heat transfer in both seasons, while the latent heat ratio slightly rose. Operational tests demonstrated that the system achieved COP ranging from 2.43 to 3.23 under typical January conditions and 3.8 to 5.0 under typical June conditions. The performance evaluation yielded a Heating Seasonal Performance Factor ( HSPF ) of 3.06, a Seasonal Energy Efficiency Ratio ( SEER ) of 4.3, and an Annual Performance Factor ( APF ) of 3.62. These results confirm the system’s favorable year-round performance and offer guidance for HTHP applications in Guizhou and similar high-humidity regions.